ANALISIS STAKEHOLDER DALAM IMPLEMENTASI KAMPUNG TEMATIK SENI DAN BUDAYA DI KELURAHAN TEMBALANG - Diyah Novitasari; Dewi Rostyaningsih (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2020)
ABSTRACT Art and Cultural Thematic Village in Tembalang Village is a part of the Semarang City poverty alleviation program based on community empowerment. The main commodity is performance art namely ketoprak and lumping horse, making this thematic village unique and the need for various parties' involvement makes stakeholder analysis important to do. This study aims to conduct stakeholder analysis and stakeholder mapping to provide strategic recommendations based on the type of stakeholder in policy implementation. This research used a qualitative research method with the case study approach. Based on the analysis of resources and values of the actors, the results showed that the co-operation type stakeholders were the Chairperson of Tembalang Village Community Empowerment Agency (LPMK), the Chairperson of the Art and Cultural Thematic Village Foundation, and the Lecturer of Undip in Thematic Community Service Program (KKN) at the Jurang Blimbing. The conformity type stakeholders are the Head of Sub-Division of Social Planning at the Regional Agency of Development Planning (Bappeda) of Semarang City and Tembalang Village community. The counter-action type stakeholder is the Deputy Chair of Ikada while the Tembalang Village Chief is included in the detachment type. Co-operation type stakeholders need to expand the network with vertical agencies such as the Semarang City Government, Central Java Provincial Government, the Ministries, and collaborate with the private sectors. Conformity type stakeholders must build stronger communication and relationships with other stakeholders to increase their resources. Counter-action and detachment type stakeholders must be given an understanding of program planning so that they understand the direction and objectives of program implementation. Detachment type stakeholders also need to increase their active participation to establish stronger relationships with other stakeholders and strengthen their influence in decision making.